IMPACT OF EDUCATION INEQUALITY ON ECONOMIC GROWTH IN OIC COUNTRIES (World Economics and Finance Bulletin, 2024)
Macroeconomic theories affirm the crucial impact of education on economic growth. Education may significantly contribute to the sustainable economic growth by enhancing human capital. Inequalities in the distribution of education among individuals result in a reduction in the overall level of human capital and have a negative impact on economic growth. Thus, this study utilized data from Organization of Islamic Cooperation (OIC) countries between 2010 and 2020 to examine the impact of educational inequality on economic growth in these nations using the Fully Modified Ordinary Least Square (FMOLS) approach. The study's results indicate a negative correlation between education disparity and economic growth, supporting the main hypothesis of the study. To achieve economic growth and ensure its longterm viability, it is essential to prioritize women's education and narrow the gender gap
Keywords: Gender Inequality; Education; Economic Growth; Organization of Islamic Cooperation (OIC) countries